Faktor Internal dan Eksternal Minat Berwirausaha dan Keberhasilan Usaha pada UMKM di Surabaya - Nagel P. Julius F.; Ani Suhartatik (Jurnal Keuangan dan Perbankan, 2018)
This study aims to examine the influence of internal and external factors on entrepreneurial interest and business success at MSMEs in Surabaya. This type of research is causal research. The sample of this study amounted to 300 people using purposive sampling techniques. The data analysis technique used is Struc-tural Equation Modeling (SEM). The results show that internal and external factors have a significant ef-fect on entrepreneurial interest and business success and entrepreneurial interest affects business success. From these results, it is known that to increase interest in entrepreneurship, the most appropriate way is to increase the internal and external factors of MSME in Surabaya. Meanwhile, to increase business success, the most appropriate way is to increase MSME entrepreneurship interests in Surabaya.